Are functional motor and sensory symptoms really more frequent on the left? A systematic review. Issue 5 (1st November 2002) - Stone, J; Sharpe, M; Carson, A; Lewis, S C; Thomas, B; Goldbeck, R; Warlow, C P
Abstract : Objectives: To test the hypothesis that unilateral motor and sensory symptoms unexplained by identifiable disease are more common on the left side of the body than the right. Methods: Systematic review of the literature published since 1965. Results: 121 eligible studies, involving 1139 patients, were analysed. The pooled proportion of functional left sided weakness and sensory symptoms in adults was 58% (95% confidence interval (CI) 55 to 61%). A much higher proportion of left sided symptoms (66%, 95% CI 61 to 71%) was found in studies where laterality featured in the title of the paper. However, when laterality was not mentioned in the title, no significant difference between left and right was observed (53% on the left, 95% CI 48 to 57%). This difference could not be explained on the basis of sex differences between the groups or the date of the study. Functional or "psychogenic" movement disorder was right sided in 68% (95% CI 61 to 75%). Handedness did not influence symptom lateralisation. Conclusions: The findings of this systematic review question whether functional weakness and sensory symptoms do in fact occur more commonly on the left side of the body. A type of outcome variable reporting bias in combination with non-blinding of investigators may be responsible for this long held but erroneous belief.